Interleukin-1β has atheroprotective effects in advanced atherosclerotic lesions of mice - Gomez, Delphine; Baylis, Richard A; Durgin, Brittany G; Newman, Alexandra A C; Alencar, Gabriel F; Mahan, Sidney; St Hilaire, Cynthia; Müller, Werner; Waisman, Ari; Francis, Sheila E; Pinteaux, Emmanuel; Randolph, Gwendalyn J; et al. (Nature medicine, 2018)
Despite decades of research, our understanding of the processes controlling late-stage atherosclerotic plaque stability remains poor. A prevailing hypothesis is that reducing inflammation may improve advanced plaque stability, as recently tested in the Canakinumab Anti-inflammatory Thrombosis Outcome Study (CANTOS) trial, in which post-myocardial infarction subjects were treated with an IL-1β antibody. Here, we performed intervention studies in which smooth muscle cell (SMC) lineage-tracing Apoe mice with advanced atherosclerosis were treated with anti-IL-1β or IgG control antibodies. Surprisingly, we found that IL-1β antibody treatment between 18 and 26 weeks of Western diet feeding induced a marked reduction in SMC and collagen content, but increased macrophage numbers in the fibrous cap. Moreover, although IL-1β antibody treatment had no effect on lesion size, it completely inhibited beneficial outward remodeling. We also found that SMC-specific knockout of Il1r1 (encoding IL-1 receptor type 1) resulted in smaller lesions nearly devoid of SMCs and lacking a fibrous cap, whereas macrophage-selective loss of IL-1R1 had no effect on lesion size or composition. Taken together, these results show that IL-1β has multiple beneficial effects in late-stage murine atherosclerosis, including promotion of outward remodeling and formation and maintenance of an SMC- and collagen-rich fibrous cap.